Quercus pyrenaica honeydew honey with high phenolic contents cause dna damage, apoptosis, and cell death through generation of reactive oxygen species in gastric adenocarcinoma cells - Koçyiğit, Abdurrahman; Aydoğdu, Gökhan; Balkan, Ezgi; Yenigün, Vildan Betül; Güler, Eray Metin; Bulut, Huri; Koktaşoğlu, Fatmanur; Gören, Ahmet Ceyhan; Atayoğlu, Ali Timuçin (SAGE, 2019)
Many studies have shown that honey with high phenolic contents prevents cancer formation. Furthermore, recent studies have demonstrated that honey can be used for the treatment of cancer as well as cancer prevention. Antineoplastic effects of honey are often associated with their antioxidant phenolic contents. However, very few studies have dealt with the association of phenolic contents of honeys in terms of antiproliferative effects. The aim of this study was, therefore, to elucidate the cytotoxic, genotoxic, apoptotic, and reactive oxygen species (ROS) generating effects of honey samples on the basis of their phenolic and flavonoid contents. Fourteen different honey varieties were collected from various parts of Turkey, and their characteristics regarding total phenols, flavonoids, and antioxidant contents were determined to test their effects on gastric cancer cells (AGS). For convenience, 2 honey varieties were selected, namely, Ida Mountains Quercus pyrenaica honeydew honey (QPHH-IM) having the highest phenolic and antioxidant content and Canakkale multifloral honey (MFH-C) with the lowest phenolic and antioxidant content. Levels of 11 different phenolic compounds in QPHH-IM and MFH-C samples were determined by LC-MS/MS. AGS cells were incubated with different concentrations of QPHH-IM and MFH-C for 24 hours, then the cell viability, DNA damage, apoptosis, and generation of ROS were determined. We found that QPHH-IM had more cytotoxic, genotoxic, and apoptotic effects than that of MFH-C. We think that these effects are probably related to pro-oxidant activities due to the high phenolic contents present. Therefore, further research on high-phenolic honey may contribute to the future development of cancer therapeutics.
Keywords: Quercus Pyrenaica; Honey; Gastric Carcinoma; Apoptosis; DNA Damage; Reactive Oxygen Species; Apitherapy